Quem sou eu e quanto posso aprender? Identidade e investimento de alunos do curso de inglês básico do Programa Nacional de Acesso ao Ensino Técnico e Emprego - Paulino, Ana Carolina Moreira (Universidade do Vale do Rio dos Sinos, 2016)
The present work aims to investigate, in the light of a theoretical spectrum coming from the areas of Applied Linguistics and Social Sciences, the relations between the representations of the English language, the identities, the imagined communities and the investment given by learners from a group of the basic English course of PRONATEC to the acquisition of the English language. The methodology used to answer the research questions was the narrative research, which guarantees, given its emic perspective, that the participants have a voice to express in their narratives their own experiences and opinions. Episodic interviews with three participants, as well as class observation in different stages of the course, accompanied by field notes, were used as instruments to generate data. The main representations of the English language observed in the participants’ narratives were the ones that see it as the language of the job market and the tourism, and that bring along with them the utilitarian bias of the language, representing it as a key to open doors that lead to a range of information and culture, and professional opportunities. It was also noticed that the learners’ identities are multiple and in continuous conflict, and that they determine when and how each one of them can express themselves. The learners’ imagined communities are mainly groups of tourism professionals who have job opportunities due to their English skills, international travelers, and even mothers who dedicate their time to their children’s educational progress. We concluded that the learners’ representations, identities and imagined communities are built through the dialog of the discourses present in the different contexts in which they take part, and that they are always permeated by relations of power, which may encourage or inhibit their investment in learning a new language.
Keywords: Representações; Identidades; Comunidades imaginadas; Investimento; PRONATEC; Representations; Identities; Imagined communities; Investment; ACCNPQ::Lingüística, Letras e Artes::Lingüística